Acquisition, Maintenance, and Ecological Roles of Kleptoplasts in Planoglabratella opercularis (Foraminifera, Rhizaria) - Tsuchiya, Masashi; Miyawaki, Seiji; Oguri, Kazumasa; Toyofuku, Takashi; Tame, Akihiro; Uematsu, Katsuyuki; Takeda, Koji; Sakai, Yuya; Miyake, Hiroshi; Maruyama, Tadashi (Frontiers in Marine Science, 2020)
Kleptoplasty or acquisition of chloroplasts from ingested photosynthetic organisms, is thought to be a key factor in determining the trophic requirements and carbon mineralization of foraminifera, consequently influencing their ecology, evolution, and calcification. However, the acquisition, maintenance, and functions of “stolen” chloroplasts (kleptoplasts) in foraminiferal cells have not been well characterized. Using molecular phylogeny and experimental measurements of oxygen flux and intracellular (vacuole) pH, we characterized aspects of kleptoplast origin and function in Planoglabratella opercularis (d’Orbigny), a rocky-shore benthic foraminifera. We determined that the kleptoplasts in P. opercularis are derived from various species of epiphytic diatoms. The acquisition of epiphytic diatoms is congruent with the behaviour of P. opercularis, which crawls on the thalli of coralline algae and grazes on the microalgae on the algal surface. Kleptoplasts were located near the host foraminiferal cell periphery, just under the pore plug, mainly along the dorsal side, which is important for oxygenic photosynthesis. The lifespan of kleptoplasts varied according to food availability and to the intensity and duration of light irradiation. Planoglabratella opercularis was able to capture not only diatom chloroplasts but also those from Chlorella. Kleptoplastids of diatom origin decreased in autofluorescence and were digested within 11 days under light in the absence of food. This suggests that host foraminifera frequently capture new diatoms to sustain kleptoplasts. Kleptoplastid autofluorescence was prolonged in the dark or 24:24-h light:dark cycle, and when food was available. Host foraminifera metabolized food to maintain the activity of kleptoplasts and effectively utilized photosynthetic products from both organic and inorganic materials in response to the ambient environment. This suggests that P. opercularis behaves as a mixotroph. Simultaneously, kleptoplasts maintain a high intracellular pH environment, indicating that foraminifera capture kleptoplasts not only to gain their photosynthates but also to control the intracellular pH levels to construct a high magnesian calcite test.